ANALISIS PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN PARIWISATA DI DESA WISATA CIBUK KIDUL - Gennosa, Caecillia Putri; Mutmainah, Nur Fitri (Universitas Bina Taruna Gorontalo, 2025)
This research aims to analyze the forms of community participation in the development of Cibuk Kidul Tourist Village, Sleman, Special Region of Yogyakarta, using the participation theory of Cohen and Uphoff (1977). In this study, the researcher employs qualitative methods with a descriptive approach. The research is located in Cibuk Kidul Tourist Village. Data collection techniques include observation, interviews with the government of Margoluwih village, managers of Cibuk Kidul Tourist Village, local communities, and documentation. Data analysis techniques involve data collection, data reduction, data presentation, and conclusion. This research shows that the community of Cibuk Kidul Tourism Village has actively participated in the development of tourism, especially in the planning and implementation stages of locally-based programs. This participation is evident from the direct role of the community in designing tourism activities, building infrastructure, and acting as key players in tourism services (such as guides, homestay managers, and culinary businesses). As a result, community income has increased and collective awareness of the village's potential has grown. However, this participation is not yet evenly distributed, particularly in the aspects of monitoring and evaluation, as well as the equitable distribution of economic benefits among community groups.